Endovascular-First Treatment Is Associated With Improved Amputation-Free Survival in Patients With Critical Limb Ischemia. Issue 8 (August 2019) - Lin, Jonathan H.; Brunson, Ann; Romano, Patrick S.; Mell, Matthew W.; Humphries, Misty D.
Abstract : Background: Critical limb ischemia remains a difficult disease to treat, with limited level one data. The BEST-CLI trial (Best Endovascular vs Best Open Surgical Therapy in Patients with Critical Limb Ischemia) is attempting to answer whether initial treatment with open surgical bypass or endovascular therapy improves outcomes, although it remains in enrollment. This study aims to compare amputation-free survival and reintervention rates in patients treated with initial open surgical bypass or endovascular intervention for ischemic ulcers of the lower extremities. Methods and Results: Using California nonfederal hospital data linked to statewide death data, all patients with lower extremity ulcers and a diagnosis of peripheral artery disease who underwent a revascularization procedure from 2005 to 2013 were identified. Propensity scores were formulated from baseline patient characteristics. Inverse probability weighting was used with Kaplan–Meier analysis to determine amputation-free survival and time to reintervention for open versus endovascular treatment. Mixed-effects Cox proportional hazards modeling was used to adjust for patient ability to manage their disease and hospital revascularization volume. A total of 16 800 patients were identified. Open surgical bypass was the initial treatment in 5970 (36%) while 10 830 (64%) underwent endovascular interventions. Patients in the endovascular group were slightly younger compared with the open group (70 versus 71 years, ±12 years; P <0.001). Endovascular-first patients were more likely to have comorbid renal failure (36% versus 24%), coronary artery disease (34% versus 32%), congestive heart failure (19% versus 15%), and diabetes mellitus (65% versus 58%; all P values <0.05). After inverse propensity weighting as well as adjustment for patient ability to manage their disease and hospital revascularization experience, open surgery first was associated with a worse amputation-free survival (hazard ratio, 1.16; 95% CI, 1.13–1.20) with no difference in mortality (hazard ratio, 0.94; 95% CI, 0.89–1.11). Endovascular first was associated with higher rates of reintervention (hazard ratio, 1.19; 95% CI, 1.14–1.23). Conclusions: Patients with critical limb ischemia have multiple comorbidities, and initial surgical bypass is associated with poorer amputation-free survival compared with an endovascular-first approach, perhaps due to increased severity of wounds at the time of presentation. Abstract : Supplemental Digital Content is available in the text.